Integrating product portfolio and supply chain design for sustainable construction - Muktar, Itai; Ailemen, Ikpefan; Uchechukwu, Okorie; Timilehin, Olubuyi (Privietlab, 2025)
This study examined the relationship between public infrastructure expenditure on information technology, electricity and economic growth using real gross domestic products as proxy. The methods of data analysis and estimation technique are Ordinary Least Square (OLS) method, Augmented Dickey Fuller (ADF) method, Unit Root Test, Johansen Co-integration Test and Error Correction Model. Data on these variables from 1981 to 2021 were sourced from the Central Bank of Nigeria Statistical Bulletin (CBN, 2021) and World Development indicators. The evidence from the long-run coefficient of public expenditure on infrastructural development has significantly impacted on economic growth, therefore infrastructure development expenditure is seen to constitute significant determinant of economic growth particularly for developing countries. The study suggested analysis of the elasticity of growth towards public expenditure on economic services and government need to take proactive and concerted effort to significantly enhance economic growth through fiscal policy targeted on sustainable economic service provision.